ANALYSIS OF WORK STRESS LEVELS AND MENTAL HEALTH AMONG WORKERS AT CILACAP REFINERY UNIT IV - Sjakbani, Sjahru; Ariyani, Nafiah; Sugiarto, Sugiarto; Sukwika, Tatan (UNG, 2025)
The oil refinery industry has a high level of risk that affects not only workers’ physical safety but also their mental health. At Cilacap Refinery Unit IV, the complexity of production processes, rotating work schedules, and operational pressures have the potential to cause work-related stress that impacts mental well-being. The novelty of this study lies in its comprehensive analysis of the relationship between work stress levels and mental health among oil refinery workers in Indonesia, taking into account job-specific factors in the oil and gas sector. The study aims to identify work stress levels, assess mental health, and analyze their relationship to produce strategic intervention recommendations. The method used is a quantitative survey with standardized questionnaires, involving respondents from Cilacap RU IV. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) through descriptive tests, Pearson correlation, and linear regression. The results showed that work stress levels were in the moderate category, while some workers exhibited mental health symptoms requiring attention. Regression analysis revealed a significant effect of work stress on mental health (p 0.05). The conclusion states that managing work stress is key to maintaining the mental health of oil refinery workers. Policy-based interventions and psychological support programs are recommended to improve workers’ well-being and operational performance.